Preparation of Metformin- loaded microspheres by ionic gelation method - الهوشي, لمى; يازجي, ليلى (Latakia University Journal -Medical Sciences Series, 2024)
Diabetes mellitus (DM) is a chronic metabolic disorder of elevated blood glucose level. Metformin is an effective agent with a good safety profile that is widely used as a first line treatment for type 2 diabetes. It has several drawbacks (eg. low oral bioavailability, short half-life, and gastrointestinal side effects). Modified release formulations of metformin have been developed to increase its tolerability and to improve patient compliance. The aim of this work is to prepare and to evaluate metformin- loaded microspheres using the ionic gelation method as a simple, low cost, and eco-friendly process to control the release of metformin hydrochloride. The microspheres were prepared using chitosan as the natural polymer and Sodium Tripolyphosphate (TPP) as a crosslinking agent, with studying the effect of different variables on microspheres characteristics. Theses variables are chitosan concentration%, TPP concentration %, drug concentration %, stirring speed, and stirring time. The prepared microspheres were further evaluated for particle shape and size, drug entrapment efficiency, percentage yield, equilibrium swelling index, and in-vitro drug release. Microscope images revealed that microspheres had spherical shape and their sizes ranged between (539-1063) µm. It was found that the F15 with (1.5% chitosan, 1.5% TPP, 1%drug, 600 rpm stirring speed, 45 min stirring time) with average particle size of (827 µm), had the highest encapsulation efficiency of (50%), percentage yield of (34%), and showed the ability to control microspheres swelling and therefore drug release in buffered gastrointestinal environment.